2009
DOI: 10.1007/978-0-387-09601-8_18
|View full text |Cite
|
Sign up to set email alerts
|

Development of Teaching in and from Practice

Abstract: except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Graeber & Tirosh, 2008;Hill, Rowan & Ball, 2005;Ma, 1999) and productive beliefs about mathematics and the learning of mathematics (e.g. Davis & Brown, 2009;Grant, Hiebert & Wearne, 1998;Phillip, 2007;Thompson, 1984). Some researchers have reported that both preservice and inservice teachers may be partially deficient in these regards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graeber & Tirosh, 2008;Hill, Rowan & Ball, 2005;Ma, 1999) and productive beliefs about mathematics and the learning of mathematics (e.g. Davis & Brown, 2009;Grant, Hiebert & Wearne, 1998;Phillip, 2007;Thompson, 1984). Some researchers have reported that both preservice and inservice teachers may be partially deficient in these regards.…”
Section: Introductionmentioning
confidence: 99%
“…First, teachers' pedagogical beliefs and teaching philosophy are known to have a profound effect on their pedagogical practice (e.g. Davis & Brown, 2009;Ozgun-Koca & Sen, 2006;Phillip, 2007;Thompson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The calculator module of this course sought to develop an understanding of issues of mathematics teaching and how students learn (Davis et al 2009). The module yielded some changes in teachers' knowledge, conceptions and practices.…”
Section: Resultsmentioning
confidence: 99%
“…Иновације у настави представљају једну од највреднијих "мантри" у образовном систему и циљ који високо истичу бројни пројекти образовних реформи у последње три деценије. Међународна искуства са увођењем иновација у школу показују да су наставничка уверења један од најзначајнијих фактора од којих зависи трајно усвајање и интеграција нових знања, вештина и пракси, што је кључно за успех иновација (Barnett & Hodson, 2001;Davis et al, 2009;Fullan, 1991;Skott, 2001;Stipek, Givvin, Salmon & MacGyvers, 2001).…”
Section: уводunclassified